A randomised controlled trial comparing compression therapy after stripping for primary great saphenous vein incompetence. (December 2019) - Krasznai, Attila G; Sigterman, Tim A; Houtermans-Auckel, Janine P; Eussen, Ed; Snoeijs, Maarten; Sikkink, Kees Jan JM; de Boer, Edith M; Wittens, Cees HA; Bouwman, Lee H
Background: Venous insufficiency of the lower extremity affects up to 40–60% of general adult population in the Western population, of which around 25% has varicose veins mostly treated by ablation of the incompetent great saphenous vein. Although endovenous options are available, the majority is still treated with stripping of the great saphenous vein for which there is no consensus regarding postoperative compressive therapy. The objective of this prospective randomised controlled trial was to evaluate 4 h compared to 72 h of leg compression after great saphenous vein stripping. Method: Patients in the Zuyderland Medical Centre with an indication for stripping of the great saphenous vein were eligible for inclusion in this study. Patients were randomised to 4 or 72 h of leg compression (standard elastic bandaging) after stripping of the great saphenous vein. Primary outcome was change in leg volume after 14 days. Secondary outcomes were post-operative pain scores, complications and time to full recovery. Results: A total of 78 patients were randomised, 36 patients enrolled the intervention (4 h) group and 42 patients the control group (72 h). The intervention group (4 h) showed a 57 mL reduction in leg volume after 14 days, compared to 6 mL of the control group (72 h) ( p  = 0.11). Post-operative pain, complications and time to full recovery did not statistically differ. Conclusion: Wearing leg compression four hours after stripping is non-inferior in preventing leg oedema compared with 72 h compression therapy. No statistically significant difference in pain and time to full recovery was shown.